Performance and Optimization of PT Beam Using Dynamic Load Condition of Larger Span Structure - Verma, Neeraj Kumar; Bandewar, Deepak Kumar (International Journal of Scientific Research in Civil Engineering, 2020)
Many of the complex behaviours of reinforced cement concrete under shear and flexure are yet to be identified to employ this material advantageously and economically. The progress in the understanding and quantitative assessment of the behaviour of member subjected to flexure and shear has been less spectacular. The fundamental nature of shear and diagonal tension strength is not yet clearly understood. So, further basic research should be encountered to determine the mechanism, which results in shear failure of reinforced concrete members. The study presents the study of the behaviour of reinforced concrete deepbeam under seismic ( vibration) loading and the effect of shear reinforcement. The influence of variation of web reinforcement spacing (both vertical and horizontal) on the shear strength of deep R.C. beam is investigated. The general trend in crack pattern, the load deflection characteristics and the mode of failure of deep R.C. beam under two-points loading are also investigated. Through the investigation, it is observed that under two-points loading system, diagonal cracks are usually the first cracks to be observed in the clear span of the deep beam. In this study we will compare deep beam with PT beam in G+10 structure using analysis tool ETABS.
Keywords: PT Beam; Bending Moment; Deflection; Shear Strength; Base Shear; Story Drift